Biolens behavior of RBCs under optically‐induced mechanical stress. Issue 5 (13th March 2017) - Merola, Francesco; Barroso, Álvaro; Miccio, Lisa; Memmolo, Pasquale; Mugnano, Martina; Ferraro, Pietro; Denz, Cornelia
Abstract: In this work, the optical behavior of Red Blood Cells (RBCs) under an optically‐induced mechanical stress was studied. Exploiting the new findings concerning the optical lens‐like behavior of RBCs, the variations of the wavefront refracted by optically‐deformed RBCs were further investigated. Experimental analysis have been performed through the combination of digital holography and numerical analysis based on Zernike polynomials, while the biological lens is deformed under the action of multiple dynamic optical tweezers. Detailed wavefront analysis provides comprehensive information about the aberrations induced by the applied mechanical stress. By this approach it was shown that the optical properties of RBCs in their discocyte form can be affected in a different way depending on the geometry of the deformation. In analogy to classical optical testing procedures, optical parameters can be correlated to a particular mechanical deformation. This could open new routes for analyzing cell elasticity by examining optical parameters instead of direct but with low resolution strain analysis, thanks to the high sensitivity of the interferometric tool. Future application of this approach could lead to early detection and diagnosis of blood diseases through a single‐step wavefront analysis for evaluating different cells elasticity. © 2017 International Society for Advancement of Cytometry